Effect of age, gender and type of varicosity on the post-operative pain score after seven-day compression dressing after varicose vein surgery - Noor Ul Ain; Rana Sohail Ahmad; Zainab Chaudhary; Mohammad Sohail Asghar; Sadaf Zafarullah; Hafiz Syed Zaigham Ali Shah (Journal of the Pakistan Medical Association, 2023)
Great saphenous vein insufficiency is linked to 80% of all remarkable lower limb varicosities. A total of 30 patients were enrolled from OPD fulfilling the inclusion criteria after the approval of the hospital’s ethical committee. Patients had compression dressing for seven days after surgery. The patients were divided into two groups—Group-A (Compression dressing for two days) and Group-B (Compression dressing for seven days). Stratification of pain score was done against age, gender, and grades of varicose veins, and after dividing into groups t- test was put into use. A p-value 0.05 was contemplated to be remarkable. Thirty patients with primary varicose vein were enrolled in this study. The mean age of patients was 35.4±9.9 years. Mean pain score in these patients was 2.9±0.8 years. —Continue